2022
DOI: 10.1039/d2nj01767a
|View full text |Cite
|
Sign up to set email alerts
|

The green design of corncob cellulose/reduced graphene oxide-derived hierarchical porous aerogels for efficient dye adsorption

Abstract: As one of the materials from natural resources, the functionalization and application of cellulose attracts more concerns. In this work, we reported a facile method to prepare the bio-inspired functionalization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Graphene aerogels can be used as adsorption materials because of their high specific surface areas, high porosities, and hydrophobicity. Combining them with functional polymers can further improve the adsorption capacity and efficiency [127][128][129][130][131][132]. For example, Zhang et al [133] reported a dimethyldiallylammonium chloride acrylamide polymer (P(AM-DMDAAC))/graphene aerogel (PGA) with high adsorption capacity and high hydrophobicity by one-step hydrothermal treatment of doping P(AM-DMDAAC) into graphene aerogel.…”
Section: Adsorption Properties and Applicationsmentioning
confidence: 99%
“…Graphene aerogels can be used as adsorption materials because of their high specific surface areas, high porosities, and hydrophobicity. Combining them with functional polymers can further improve the adsorption capacity and efficiency [127][128][129][130][131][132]. For example, Zhang et al [133] reported a dimethyldiallylammonium chloride acrylamide polymer (P(AM-DMDAAC))/graphene aerogel (PGA) with high adsorption capacity and high hydrophobicity by one-step hydrothermal treatment of doping P(AM-DMDAAC) into graphene aerogel.…”
Section: Adsorption Properties and Applicationsmentioning
confidence: 99%